2(5x-3)-2x+7=

Simple and best practice solution for 2(5x-3)-2x+7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5x-3)-2x+7= equation:


Simplifying
2(5x + -3) + -2x + 7 = 0

Reorder the terms:
2(-3 + 5x) + -2x + 7 = 0
(-3 * 2 + 5x * 2) + -2x + 7 = 0
(-6 + 10x) + -2x + 7 = 0

Reorder the terms:
-6 + 7 + 10x + -2x = 0

Combine like terms: -6 + 7 = 1
1 + 10x + -2x = 0

Combine like terms: 10x + -2x = 8x
1 + 8x = 0

Solving
1 + 8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 8x = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 8x = 0 + -1
8x = 0 + -1

Combine like terms: 0 + -1 = -1
8x = -1

Divide each side by '8'.
x = -0.125

Simplifying
x = -0.125

See similar equations:

| -5(3t-2)+7t=4t-9 | | 3x-7+6x+2= | | -5(3t-2)+4t=8t-6 | | -14+n=-11 | | 2X^2+19x+80=0 | | 54=-3/4p | | 9x+y=-26 | | f(0)=(2x^(2)-10)/(7x-5) | | 1.21x=3.2 | | 3.2x=1.21 | | X+-11=-12 | | -2(a+3)-5=-4(a-2)+1 | | 3(7m+4)+5=6(5m-3)-4m | | -21+8+3x= | | 5(2c+4)+4c=8(3c-2)+6 | | -1=3t-19 | | 7=w-(-7) | | 4(x+1)+2x=3(x+5)+1 | | 4+5a=-16 | | 4a-2c/2 | | 2(3a+5)+4=3(3a+2)-a | | 3(4m+5)+6m=8(3m-2)-7m | | 3(4m+5)+6m=5(6y+3)-8 | | 3x+40=320 | | 4x^2-x^2-81=0 | | 10(3a-5)+8=9(4a+3)-5a | | x^2-2x-74=0 | | 4(7y+2)+y=5(6y+3)-8 | | 6(2w+8)+3w=2(10w-5)-4w | | 8(4n+3)-5=7(5n-4)-2n | | 4(2m+3)+4=2(5m+4)-m | | 2(x-4)=m(1+x) |

Equations solver categories